Free-trade: abolition of customs and excise duties; and a sketch of a simpler and better mode of raising a Revenue - Haughton, James (Statistical and Social Inquiry Society of Ireland, 1864)
Among those many useful topics to which I have alluded, the discussion of Free-trade, and its partial adoption by us, and other nations, has been attended with many beneficial results. It is my main object in this paper to press on our members, and on the community at large, the necessity for the full and complete adoption of this principle, in all our commercial relations throughout the world. Whatever may be the delays in carrying out to its full completion this great principle for bringing mankind into more peaceful relations, and in extending the traffic with all nations, which results in the greatest good to all, whatever difficulties may impede its its grand and speedy consummation, I have no doubt of its ultimate success among all civilized nations. The march of the great truth, that it is for the interest of all, to leave trade as free as those winds of heaven which waft our ships round the world, cannot now be much longer arrested by ignorance or cupidity. Every impediment which yet stands in the way of free intercourse, must be removed; and the sooner these great commercial nations of which we form a part, sweep them all away, the better it will be for us all?the happier, the wealthier, and the more steadily prosperous, our people will be.
Read Wednesday, 20th April, 1864
Keywords: Free trade; Commerce; 314.15